2021
DOI: 10.3390/jcm10050912
|View full text |Cite
|
Sign up to set email alerts
|

ACL Repair: A Game Changer or Will History Repeat Itself? A Critical Appraisal

Abstract: Until the past decade the common thought was that the anterior cruciate ligament (ACL) was not able to heal and restore knee stability. In this manuscript a brief review of studies of the developers and the early adaptors of four different modern ACL repair techniques are presented. The present status and considerations for the future of ACL repair and its research are shared. After promising short- to midterm ACL healing results by the developers, the results of the early adaptors show more variety in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 73 publications
0
29
0
4
Order By: Relevance
“…MRI and histology thus permitted in the present model to objectivate the absence of spontaneous healing 12 weeks after ACL transection without associated reconstruction. Some authors allocated the absence of spontaneous ACL healing to the gap formed between the ACL ends and subsequent interposition of synovial fluid, which impair the possibility of a guided regeneration process [5]. Indeed, healing of ACL remnants has been previously observed on histology 12 weeks after surgery in a goat model of mid-substance transection followed by locking suture, alone or combined with small intestine submucosa [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI and histology thus permitted in the present model to objectivate the absence of spontaneous healing 12 weeks after ACL transection without associated reconstruction. Some authors allocated the absence of spontaneous ACL healing to the gap formed between the ACL ends and subsequent interposition of synovial fluid, which impair the possibility of a guided regeneration process [5]. Indeed, healing of ACL remnants has been previously observed on histology 12 weeks after surgery in a goat model of mid-substance transection followed by locking suture, alone or combined with small intestine submucosa [56].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is still lacking in people regarding the superiority of ACL reconstructive surgery over conservative management on post-traumatic OA [2,61]. Some studies even suggested a worse OA long-term prognosis for operated ACL-deficient knees compared to knees treated conservatively [5]. Experimental studies in animals demonstrated that ACL reconstruction did not protect cartilages from degenerative changes [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Biologically augmented ACL repair is an upcoming approach to overcome this osteoarthritis and as well give a similar biomechanical outcome. 25,26…”
Section: Repair Techniquesmentioning
confidence: 99%
“…Кожна методика потребує ретельного підходу до вибору "випадок -пацієнт", однак результатів досліджень недостатньо, щоб розглядати ці способи в контексті стандартизованого підходу. Найбільш вагомими є дослідження S. Kohl, D. Evangelopoulos (2013) та H. Christiaan, W. Heusdens (2021) щодо застосування методики DIS як способу відновле ння ПСЗ [40,41]. Ця фіксація передбачає ушивання ушкодженої ділянки ПСЗ полідіоксаноновим шовним матеріалом та стабілізацію колінного суглоба швом, який проходить поряд із ПСЗ та фіксується на великогомілковій кістці за допомогою пружинно-гвинтової системи.…”
Section: вступunclassified